PCR-RFLP based identification of duplicated DQA loci in riverine buffalo - Saket Kumar Niranjan; Arjava Sharma; Sitangsu Mohan Deb; Soumen Naskar; Durgam Sakaram (Journal of Livestock Biodiversity, 2025)
Major histocompatibility complex (MHC) DQ genes are highly polymorphic and duplicated in bovines including buffalo. Duplication of DQ genes seems to generate greater genetic diversity, which causes better recognition of wider range of pathogens. In this study, we devised the PCR-RFLP based genotyping method for rapid identification of duplicated haplotypes at DQA locus in riverine buffaloes. Genomic region corresponding to Bubu-DQA exon 2 to 3 was amplified from 152 buffaloes belonging to Murrah and Bhadawari breeds. Three primers were multiplexed for PCR amplification to amplify both loci. RFLP analysis obtained through digestion of amplified products by Ava II restriction enzyme revealed five different patterns. A total of three major haplotypes carrying either DQA1 only or DQA2 only or both DQA1 and DQA2 were identified. About more than half of the buffalo population was found to have duplicated haplotype carrying DQA1 and DQA2 genes. This simple, rapid and reliable PCR-RFLP technique can be used for the identification of duplicated DQA haplotypes in buffalo population.